Risk Factors for Unplanned ICU Readmission Among Trauma Patients: Age Matters - Adam D. Laytin, MD, MPH; Carrie A. Sims, MD, PhD (Critical Care Explorations, 2022)
OBJECTIVES:. To determine the frequency of unplanned ICU readmission (UIR) among adult (18–64) and elderly (65+) trauma patients and to compare the risk factors for UIR and its clinical impact between age groups. DESIGN:. Retrospective cohort study using clinical data from a statewide trauma registry. SETTING:. All accredited trauma centers in Pennsylvania. PATIENTS:. Consecutive adult and elderly trauma patients requiring admission from the emergency department to the ICU between 2012 and 2017. INTERVENTIONS:. None. MEASUREMENTS AND MAIN RESULTS:. Among the 48,340 included in the analysis, 49.5% were elderly and 3.8% experienced UIR. UIR was 1.7 times more likely among elderly patients and was associated with increased hospital length of stay in both age groups. UIR was associated with an absolute increased risk of hospital mortality of 6.1% among adult patients and 16.9% among elderly patients experiencing UIR. In addition to overall injury severity and burden of preexisting medical conditions, specific risk factors for UIR were identified in each age group. In adult but not elderly patients, UIR was significantly associated with history of stroke, peptic ulcer disease, cirrhosis, diabetes, and malignancy. In elderly but not adult patients, UIR was also significantly associated with chronic kidney disease. CONCLUSIONS:. UIR is associated with worse clinical outcomes in both adult and elderly trauma patients, but risk factors and the magnitude of impact differ between age groups. Interventions to mitigate the risk of UIR that take into account patients’ age group and specific risk factors may improve outcomes.